Consequences of patellar tendinopathy on isokinetic knee strength and jumps in professional volleyball players - Chantrelle, M.; Menu, P.; Gernigon, M.; Louguet, B.; Dauty, M.; Fouasson-Chailloux, A. (Sensors, 2022)
Patellar tendinopathy (PT) in professional volleyball players can have an impact on their careers. We evaluated the impact of this pathology in this specific population in terms of isokinetic strength and jumping performances. Thirty-six professional male volleyball players (mean age: 24.8 ± 5.2) performed isokinetic knee assessments, single-leg countermovement jumps and one leg hop test. They filled out the Victorian Institute of Sport Assessment-Patella (VISA-P) score. Two groups were assessed: "PT group" (n = 15) and "control group" (n = 21). The VISA-P score was lower in the PT group (p < 0.0001). No difference was found between the isokinetic strength limb symmetry index and the jump performance limb symmetry index. The healthy legs of the control group were compared with the affected (PT+) and the unaffected legs (PT-) of the PT group. Compared with the healthy legs, both PT+ and PT- legs showed decreased values of quadriceps and hamstring strengths. Only PT+ legs scored lower than healthy legs in countermovement jumps and hop tests. No differences were found between PT+ and PT- legs for muscle strengths and jumps. A low correlation existed between quadriceps strength and jumping performances (r > 0.3; p < 0.001). Volleyball players with PT showed a decrease in the isokinetic knee strength. This strength deficit was found both on the symptomatic legs and the asymptomatic ones. Jumps were only significantly altered on the pathological legs. Highlighting that the unaffected limbs were also impaired in addition to the affected limbs may help provide a better adaptation of the rehabilitation management.